(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Although education is considered a necessity, more and more parents areeducating their daughters still learning household work for a girl is givenimportance. They cannot negate house hold work to most of women their daughtersare helpful in household duties. Katai (1939) study perceived that householdwork was still the responsibility of working women.